IN THE POSSIBLE TOMORROW - González B., Yeslando (IJRDO- Journal of Educational Research, 2018)
Believe it or not, in international bodies responsible for reviewing global education policies in the face of the challenge that faces humanity by 2030, is one of the biggest challenges for educators in a possible tomorrow. But private commitments are not enough, even if they are plural and in truth they are nothing more than virtual realities of empty discussions where, unquestionably, the least favored have no voice to represent them. The following work tries through the discursive method an existential and psychological analysis of some political positions towards the education of the new millennium.